A COF-based anti-interference nanoplatform for intracellular nucleic acid imaging. Issue 91 (30th October 2020) - Gao, Peng; Wang, Mengzhen; Wan, Xiuyan; Liu, Xiaohan; Pan, Wei; Li, Na; Tang, Bo
Abstract : A porphyrin covalent organic framework-based nanoplatform was demonstrated. The nanoplatform could effectively avoid the interference of proteins and biothiols and realize high-fidelity mRNA imaging in living cells. Abstract : We demonstrate here that a porphyrin covalent organic framework-based nanoplatform could effectively avoid the interference of proteins and biothiols and result in high-fidelity signals in intracellular mRNA imaging.